“If I could read your mind…”: parental mentalizing in mothers with borderline personality disorder - Jana Zitzmann; Anna Georg; Charlotte Rosenbach; Babette Renneberg (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background Individuals with a borderline personality disorder (BPD) show impairments in their ability to mentalize. Particularly in the parent-child relationship, mentalizing is an important foundation for sensitive parenting and the quality of interactive behavior. Previous studies of parental mentalizing in mothers with BPD are scarce and have focused primarily on one aspect of the multidimensional construct. In addition, there is currently no research comparing different mental disorders on different aspects of parental mentalizing, leaving disorder-specific differences unclear. Aim of this study is to examine disorder-specific differences in reflective functioning and mind-mindedness, two facets of parental mentalizing. Methods We compared mothers with BPD (n = 156) with a clinical control group of mothers with depressive or anxiety disorders (n = 65) and with healthy mothers (n = 91) using non-parametric inference for multivariate data. Mothers completed the Parental Reflective Functioning Questionnaire (PRFQ) and participated in a five-minute speech sample (FMSS) in which they reflected on their child and their relationship with their child. Verbal transcripts of the FMSS were rated using an adapted manual for coding mind-mindedness with the FMSS that incorporates the assessment of additional characteristics of mind-related speech. Results Mothers with BPD showed the highest impairments in parental mentalizing compared to both other groups, as evident in both operationalizations: They made more maladaptive attributions (PRFQ pre-mentalizing) than the other two groups and reported lower interest and curiosity and certainty in mental states than healthy mothers. In addition, mothers with BPD used more mental attributes with negative valence when asked to describe their child and the relationship compared to both other groups and more self-related mental attributes compared to healthy mothers. Additionally, Pearson correlational analyses revealed that only the use of mental attributes with negative valence was associated with all three subscales of the PRFQ in the anticipated directions. This supports the idea that the two operationalizations target different facets of parental mentalization. Conclusions Our findings revealed impaired parental mentalization in several domains for mothers with BPD. Disorder-specific differences were observed in the amount of maladaptive attributions and in the negativity of mental state references. These aspects should be considered in diagnostic and therapeutic processes when working with mothers with BPD. As a limitation, it should be noted that the group comparisons did not control for sociodemographic variables, which may have contributed to some of the observed group differences.